The digital photography book. the step-by-step secrets for how to make your photos look like the pros'! - Kelby, Scott (Peachpit Press, 2013)
Furnishes an overview of digital photography, covering such topics as cameras, exposure, lighting, shutter speed, depth of field, and resolution--and tips on how to avoid hours of photo-editing by taking great photographs the first time.